Comparison Of Traffic Noise Level Assessment Between Industrial Areas, Residential Area And Construction Areas In Ipoh, Perak - Zain, Wan Mohd Nainunis Wan Md (Universiti Sains Malaysia, 2021)
This study focuses on the measurement of traffic noise in the Ipoh, Perak area involving different land-use areas, namely residential zones, industrial zones and construction zones. Among the areas involved in this study are the Meru Impian housing area, the Menglembu industrial area and the Meru Perdana construction area. A total of 10 sampling points were set for each study area. The Decibel-X Pro application was used to replace the sound level meter device to record traffic noise levels for 15 minutes for each sampling point. These readings were recorded for three different times, namely in the morning, afternoon and evening. This noise level is recorded during peak hours between 7.30 am - 9.30 am (morning), 12.00 pm - 2.00 pm (noon) and 5.00 pm - 7.00 pm (evening). Different areas or sampling points would have different characteristics, therefore, different noise exposure limit would be obtained. Manual calculation of traffic density is also measured simultaneously with noise measurement according to the Road Technical Instructions (8/86), Road Geometry Design Guide (cars, motorcycles, small trucks and heavy vehicles). The LAeq noise levels recorded in these areas ranged from 55 dB (A) to 75 dB (A). The average sound level (LAeq) recorded were exceeded the maximum permissible sound level (LAeq) according to the Planning Guidelines for Receiving Land Use for Planning and New Development for Environmental Noise Limits and Control by the Department of Environment. This study proved that there are various relationship between traffic noise levels and traffic composition which show that the noise levels decreases when the traffic composition increases and also the other way round. This event influenced by the difference speed of the vehicles and the noise produced by each vehicle is different.